1998
DOI: 10.1620/tjem.186.121
|View full text |Cite
|
Sign up to set email alerts
|

Signet Ring Cell Carcinoma of the Stomach: A Clinicopathological Comparison with the Other Histological Types.

Abstract: A retrospective analysis was carried out on 93 patients with signet ring cell carcinoma of the stomach operated on between 1985 and 1995, to review the clinicopathologic characteristics from the database of gastric cancer at Sendai National Hospital. The results were compared with those for 590 patients with other types of gastric carcinoma. Women were afflicted as commonly as men in the signet ring cell carcinoma group. These patients tended to be younger and to have larger tumors. The histological type was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
1
8

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(80 citation statements)
references
References 13 publications
4
67
1
8
Order By: Relevance
“…2 Stage-stratified survival curves for the non-SRC and SRC groups was found more frequently during surgery in patients with SRC-type gastric carcinoma [7,33,35]. Accordingly, Asian studies reported that the SRC histological type exhibited a lower curative resection rate and was associated with poorer overall survival [7,10,11,22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Stage-stratified survival curves for the non-SRC and SRC groups was found more frequently during surgery in patients with SRC-type gastric carcinoma [7,33,35]. Accordingly, Asian studies reported that the SRC histological type exhibited a lower curative resection rate and was associated with poorer overall survival [7,10,11,22].…”
Section: Discussionmentioning
confidence: 99%
“…Although the global incidence of gastric adenocarcinoma has declined in the last few years, the incidence of the signet-ring cell (SRC) type increased in the USA between 1973 and 2000 from 0.1 to 1.4 cases per 100,000 persons [2], and represents 3.5 % to 45.4 % of gastric carcinoma in recent publications [3][4][5][6][7][8][9][10][11][12]. According to the World Health Organization (WHO) classification, SRC carcinoma is an adenocarcinoma in which more than 50 % of the tumor consists of isolated or small groups of malignant cells containing intracytoplasmic mucins [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathological data showed that GS003 sample collected from the surrounding tissue of a signet-ring carcinoma was high grade atrophy with high grade intestinal metaplasia. Signet ring cell gastric carcinoma was characterized by poor differentiation, strong invasive tendency, and poor prognosis with invading surrounding tissue in a diffuse manner (Yokota et al, 1998;Kim et al, 2004). In many patients with signet ring cell gastric carcinoma, infiltration and metastasis happens earlier before the lesions could be seen by naked eyes through gastroscopy.…”
Section: Potential Role Of Collagens In Gastric Cancermentioning
confidence: 99%
“…Ninety-nine percent of signet ring cell carcinomas originate in the stomach. 5 Because gastric cancer is the most likely diagnosis, EGD would be helpful to definitively locate the primary cancer. However, our patient has distant metastasis, and thus further invasive diagnostic testing is not absolutely necessary.…”
Section: Which One Of the Following Laboratory Tests Ismentioning
confidence: 99%